2021
DOI: 10.1590/0104-1428.20210057
|View full text |Cite
|
Sign up to set email alerts
|

Role of cellulose nanocrystals in epoxy-based nanocomposites: mechanical properties, morphology and thermal behavior

Abstract: This study evaluated the influence of cellulose nanocrystals (CNC) content on the properties of epoxy nanocomposites. The CNC were obtained from microcrystalline cellulose by acid hydrolysis. 4.0, 5.5 and 7.0% of untreated CNC were incorporated into epoxy resin. Sonication was used to disperse the CNC in the resin. The thermal stability, the glass transition temperature and the degree of conversion were reduced as observed by Thermogravimetry and Differential Scanning Calorimetry, respectively. The tensile and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Although the addition of 4.5% CNC in PLA-gelatin multilayer films significantly reduced the tensile strength and elongation, this nanocomponent was not a viable alternative to reinforce this polymeric matrix [ 22 ]. When the nature of the reinforcement material and the polymeric matrix are not the same, this low compatibility can be seen as a weakness in terms of mechanical properties, i.e., the same effect as that generated when the nanomaterials have not been uniformly dispersed in the structural matrix material [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the addition of 4.5% CNC in PLA-gelatin multilayer films significantly reduced the tensile strength and elongation, this nanocomponent was not a viable alternative to reinforce this polymeric matrix [ 22 ]. When the nature of the reinforcement material and the polymeric matrix are not the same, this low compatibility can be seen as a weakness in terms of mechanical properties, i.e., the same effect as that generated when the nanomaterials have not been uniformly dispersed in the structural matrix material [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The thermal stability for epoxy/CNF is superior for additive concentrations up to 0.75 wt.%, owing to the favorable interactions in parallel with the previously noticed increase in the T g . However, the lower thermal stability at 1.0 to 1.5 wt.% CNF has also been noticed before and attributed to the percolation threshold volume fraction causing increased thermal conductivity [ 55 ]. Alternatively, the drop in the thermal stability at high nanocellulose concentrations can be attributed to unreacted nanocellulose and epoxy after incomplete mixing.…”
Section: Resultsmentioning
confidence: 75%
“…The chemical modification also improved the micro-wear characteristics of CNC/epoxy nanocomposite coatings [ 51 ], while a general improvement in mechanical properties [ 52 ] and abrasive wear properties was reported for UV-crosslinked waterborne epoxy coatings with modified CNC [ 53 ]. In comparison, the low concentrations of up to 1 wt.% unmodified CNC also improved the mechanical strength [ 54 ], thermal behavior [ 55 ], and impact resistance [ 56 ], although proper dispersion was required and processing through solvent exchange was needed. The chemical, mechanical, physical, and thermal properties of the epoxy coatings with 0.2 to 0.7 wt.% pure CNC improved with very little aggregation [ 57 ], while further improvement with up to 2 wt.% CNC was observed after surface modification [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several authors studied the influence of nano-reinforcements on the properties of the material. The experimental campaign of Nacimento et al [1] revealed an increase in Young's modulus and a decrease in strength of CNC/epoxy nanocomposites. Saba et al [2], studied cellulose nanofibers epoxy resin which exhibited an increase in all measured properties at 0.75% w/w content of reinforcement.…”
Section: Introductionmentioning
confidence: 99%